Second Time Exploration the Essence of the Universe (London Journal of Research In Humanities and Social Sciences, 2024)
The previous paper ” Exploration the Essence of the Universe” （liu，（2024）discussed the issues of time and space. This article mainly discusses the existence within space. What is the existence in space? Existence can express the form and the nature of space，Existence and can perceive force and time. The name of space“tan（怹）”in the article，show reverence for space；。Don’t use the name it (它).
Keywords: The Space The Existence Basic Energy Intellectual Energy The Time The Energy The Information Matter Cosmic origin